Vigílias do Conselho de Segurança Nacional durante a ditadura civil-militar brasileira: prospecções de um regime de informação sobre a Justiça Militar - Corrêa, Gabriel Bernardo (2019)
The present work is an exploratory study, based on a methodological proposal close to the classification studies, on the cassation processes produced by the National Council for National Security (CSN)A kind of “dossier process”, about the auditing judges allocated in the Military Justice who had their positions revoked based on Institutional Act No. 5 (AI-5), between 1969 and 1970. These cassations belonged to the set of actions that make up the National Security policy during the military dictatorship in Brazil. The relevance of this research object is in the identification of how the Information Regime was presented in the figure of the CSN as responsible for documenting and filing cassation processes on the magistrates, who mediated the trial of countless civilians convicted during the dictatorship. In other words, its modus operandi is the material evidence of the Information Regime at the time. These documents are made up of reports from various information agencies of the Brazilian government that, even today, represent a technical (legal) and political memory about the perspective of how the instituted informational state interpreted and acted on National Security Law. The objective of this study was to identify the vulnerability of the Military Justice submitted to the dictatorship; analyzing the main documents on the subject: the cassation processes housed in the National Archives of Brazil. This study also sought to test the construction of an exploratory methodology for the analysis of documents of a historical nature and of the Brazilian judiciary with a view to the field of Information Science. The results show that the contents of the analyzed documents were used arbitrarily and with the purpose of informing the regime of public and private order practices of the magistrates.